Kerangka Arsitektur Enterprise Berbasis TOGAF untuk Standar Proses Persiapan Pembelajaran Perguruan Tinggi - Suryo Widiantoro (Prosiding, 2022)
The Internal Quality Assurance System (SPMI) has become a must for universities in Indonesia in carrying out all their academic activities, including the tridharma of higher education. This system aims to enable universities to provide quality higher education services in accordance with standards so that they can produce graduates who are also of high quality. One of the standards implemented is for the learning preparation process. For this reason, information technology support is needed that can help carry out learning preparation so that it can function properly. A common problem is that the existing systems are not yet integrated because they are built based on momentary needs and not designed as a whole as a unified whole. This study aims to provide a study and a brief description of the application of enterprise architecture in mapping information technology to serve the implementation of learning preparation standards in universities. The Open Group Architecture Framework (TOGAF) provides a framework that can show the architecture of integrated information systems and technology based on the organization's business needs so as to achieve alignment between existing business and technology. The Architecture Development Methods (ADM) as part of TOGAF is the method used in developing the SPMI architecture framework for higher education because the stages in it are considered complete enough to design a harmonious vision, business, information system, and technology architecture. The result of the research is a comprehensive and efficient architectural conceptual framework from the learning preparation process to information systems and supporting technology which is expected to be a reference for universities to carry out good practices in implementing their internal quality assurance systems.